Economic Resilience in European Dairy Farms: Trends, Determinants and Challenges - Artur Wilczyński; Ewa Kołoszycz (Amfiteatru Economic)
In the face of increasing economic challenges and changing market conditions, farm resilience is becoming a key issue to ensure its development. The aim of this paper is to analyse the level of economic resilience of farms specialising in dairy farming in the ten largest dairy-producing countries of the European Union between 2004 and 2021. The research applies a self-modified multidimensional index of economic resilience, which includes elements such as vulnerability, intensification, biodiversity, diversification, and performance. The results show a decrease in economic resilience in the analysed farm groups, regardless of their economic size. It was also found that farms with a larger economic size did not demonstrate higher economic resilience compared to farms with a smaller size. The research results indicate a downward trend in the economic resilience index from 2004 to 2021. The key dimensions that affected this indicator were intensification and diversification. This suggests that, to increase their resilience, the dairy farms studied must address challenges such as reducing input use intensity, minimising dependence on hired labour, and diversifying income sources.